177k views
5 votes
For the following system, if you isolated x in the first equation to use the substitution method, what expression would you substitute into the second equation? −x + 2y = −6 3x + y = 8

User Kadina
by
5.1k points

2 Answers

4 votes

Explanation:

Start by solving the equation for x (☓)


- x + 2y = 6 \\ \: \: \: \: \: 3 + y = 8


x = 6 + 2y

Substitute the given value of x for the equation 3 + y = 8


3(6 + 2y) + y = 8

solve the equation for y


y = - (10)/(7)

substitute the given value of y into the equation x = 6 + 2


x = 6 + 2 * ( - (10)/(7) )

solve the equation for x


x = (22)/(7)

The possible solution of the system is the ordered pair (x,y)


((22)/(7) . - (10)/(7) )

The dot (.) in the center is supposed to be a comma but the scientific keyboard does not support a comma


(x.y) \: \: ( (22)/(7) . - (10)/(7) )

This is the solution

Marnie out!

User Earachefl
by
5.2k points
2 votes

Answer:


x=2y+6

Explanation:

So we have the system:


-x+2y=-6\\3x+y=8

If we isolate the x-variable in the first equation:


-x+2y=-6

Subtract 2y from both sides:


-x=-6-2y

Divide both sides by -1:


x=2y+6

Therefore, we would substitute the above into the second equation:


3x+y=8\\3(2y+6)+y=8

The answer is 2y+6

Further notes:

To solve for the system, distribute:


6y+18+y=8

Simplify:


7y+18=8

Subtract:


7y=-10

Divide:


y=-10/7\approx-1.4286

Now, substitute this value back into the isolated equation:


x=2(-10/7)+6\\x=-20/7+42/7\\x=22/7\approx3.1429

User Jeroen Steenbeeke
by
4.8k points